House fly, Musca domestica Linnaeus (Insecta: Diptera: Muscidae) - H. Sanchez-Arroyo; John L. Capinera (EDIS)
This document provides an in-depth profile of the house fly, Musca domestica Linnaeus, detailing its life cycle, distribution, and medical importance. Originating from central Asia, the house fly is now found globally, thriving in various environments. It undergoes complete metamorphosis and can produce numerous generations annually. House flies are significant pests, capable of transmitting pathogens and causing health issues. Effective management includes sanitation, traps, biological control, and selective insecticide use. The document emphasizes the importance of integrated fly control programs for maintaining public health and comfort. Original publication date August 1998.